A Process Model of Goal Orientation and Feedback Seeking - PARK, Guihyun Grace (Institutional Knowledge at Singapore Management University, 2007)
This study investigated antecedents of seeking different types of feedback. Individual differences in goal orientation and cost and value perceptions were proposed as antecedents of seeking different types of feedback. We hypothesized that 4 dimensions of cost and value perceptions of feedback seeking (expectancy value, appraisal value, ego cost, and self-presentation cost) are related to an individual's goal orientation. Furthermore, moving beyond a focus on the frequency of feedback seeking, we proposed that the perceptions of costs and values of feedback seeking influence the preference for and choice among 4 distinct feedback types (diagnostic, normative, assurance, and no feedback). A total of 240 students participated in a computer-simulated work setting. Results were largely consistent with the hypotheses; each goal orientation had a unique pattern of relations with the perceptions of costs and values. Cost and value perceptions, in turn, influenced preference and choice for feedback type. The theoretical implications of the research are discussed.